2015
DOI: 10.1038/srep13300
|View full text |Cite
|
Sign up to set email alerts
|

Association of p53 rs1042522, MDM2 rs2279744 and p21 rs1801270 polymorphisms with retinoblastoma risk and invasion in a Chinese population

Abstract: Single nucleotide polymorphisms (SNPs) of p53 rs1042522, MDM2 rs2279744 and p21 rs1801270, all in the p53 pathway, which plays a crucial role in DNA damage and genomic instability, were reported to be associated with cancer risk and pathologic characteristics. This case-control study was designed to analyse the association between these SNPs and retinoblastoma (RB) in a Chinese Han population. These SNPs in 168 RB patients and 185 adult controls were genotyped using genomic DNA from venous blood. No significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 56 publications
0
40
0
Order By: Relevance
“…[ 83 ] It was observed from XPS spectra that there is very slight difference of Cu 2p spectra between AuCu and AuCu 3 , indicative of no visible charge transfer between Au and Cu, which is at odds with our general knowledge that Au is the most electronegative and electronwithdrawing metal. [ 18,102,103 ] Lattice strain effect, generated as a consequence of intrinsic twinned structure as well as lattice mismatch between core and shell metals, is regarded as the only infl uencing factor able to spread along several atomic layers to the particle surface. This change is reasonably attributed to the shielding effect, because Au 5d orbitals lose charge and 6sp orbitals gain charge, which speaks to stronger shielding effect imposed on 4f orbitals from localized 5d electrons; therefore, the ascending of d-band center induced by charge loss in d band causes even higher electron binding energy of 4f orbital.…”
Section: Tuning Of Bimetallic Catalystsmentioning
confidence: 99%
“…[ 83 ] It was observed from XPS spectra that there is very slight difference of Cu 2p spectra between AuCu and AuCu 3 , indicative of no visible charge transfer between Au and Cu, which is at odds with our general knowledge that Au is the most electronegative and electronwithdrawing metal. [ 18,102,103 ] Lattice strain effect, generated as a consequence of intrinsic twinned structure as well as lattice mismatch between core and shell metals, is regarded as the only infl uencing factor able to spread along several atomic layers to the particle surface. This change is reasonably attributed to the shielding effect, because Au 5d orbitals lose charge and 6sp orbitals gain charge, which speaks to stronger shielding effect imposed on 4f orbitals from localized 5d electrons; therefore, the ascending of d-band center induced by charge loss in d band causes even higher electron binding energy of 4f orbital.…”
Section: Tuning Of Bimetallic Catalystsmentioning
confidence: 99%
“…The enhancement of catalytic performance and possible discovery of unique properties is still the main force driving the designing of novel nano-catalysts and sub-nanometre cluster catalysts. The Pd-Au bimetallic system, for example, exhibits high durability and catalytic activity for many interesting chemical reactions, such as the electro-oxidation of ethanol [17,18], the Suzuki coupling reaction [19], and the oxygen reduction reaction [20].…”
Section: Introductionmentioning
confidence: 99%
“…30 Furthermore, Akulevich et al found the correlation of rs1042522 with the higher risk of radiogenic PTC in Caucasians (OR = 1.80, 95% CI 1.06-2.36). 17 The protective effects of GC (Arg/Pro) genotype against retinoblastoma 21 and C (Pro) allele against endometrial cancer 31 and colorectal cancer 32 have been reported previously. Dehghan et al found no significant difference between Arg72pro genotypes in Iranian patients with differentiated thyroid cancer and control group.…”
Section: Discussionmentioning
confidence: 75%
“…It has been shown that C > A substitution in rs1059234 at codon 31 of the P21 protein (nonsynonymous serine-toarginine substitution, p.Ser31Arg) alters DNA binding of zinc finger motif and expression of P21. 21 Also, the rs1059234 polymorphism, in the 3'untranslated region of P21 affects mRNA stability and alters the level of protein expression and is implicated in the proliferation, differentiation, and tumor inhibition. 19 In this study, we analyzed TP53-rs1042522, P21-rs1801270, and P21-rs1059234 polymorphisms in southeast Iranian PTC patients and control group.…”
Section: Introductionmentioning
confidence: 99%